Mechanisms for citizen participation in Ecuadorian municipal public radios: The Role of Municipal Public Media - Marchán Luna, Teresa; Del Campo Saltos, Guillermo Segundo; Córdova Medina, Héctor Manuel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The study aimed to analyze mechanisms used by Ecuadorian municipal public radios to promote citizen participation. Eighteen of the twenty-two identified stations voluntarily participated in surveys, providing insights into compliance with national laws, internal regulations, and other citizen engagement efforts. It was noted that these radios primarily relied on public funding, which lacked specific legal backing, making them subject to prevailing political will. Compliance with operational regulations was inconsistent, with a general lack of awareness, resulting in low citizen involvement in content design. These findings underscore the need to strengthen relevant legislation and promote more active community participation in these stations..